Spatial imbalance and factors influencing carbon emission efficiency in China’s transport industry - Ma, Qifei; Jia, Peng; Kuang, Haibo (Frontiers in Earth Science, 2022)
Exploring the regional differences of transport carbon emission efficiency (TCEE) and accurately identifying its influencing factors are crucial for achieving carbon neutrality in transport industry as soon as possible. The TCEE of 30 provinces in China from 2003 to 2018 was measured, and its spatial imbalance and influencing factors were determined. The following conclusions are drawn. First, previous studies have shown that the TCEE is increasing at an overall low level with significant regional differences. Second, the total regional differences of China’s TCEE presents a trend of rising first and then falling, and the intra-regional differences are the main source of total differences. Third, this study shows that certain factors, such as the economic level, transport structure, energy structure, and technical level, significantly influenced the TCEE, but there were notable spatial-temporal differences in each factor. Finally, targeted and differentiated carbon emissions reduction policies were proposed for transport departments to realize carbon neutrality as rapidly as possible.